Psyche and human thought from the anatomies of the past - Ciliberti, Rosagemma; Fusco, Roberta (Acta Biomedica Atenei Parmensis, 2023)
De Blasio’s research focuses on the anthropology of the late 19th and early 20th centuries. His investigations extend from criminalistics to ancient mummies, driven by his passion for archaeology and human history. He delves into the intricate relationship between anatomy and the human psyche, intertwining disciplines like archaeology, anthropology, and history. His examination of ancient human remains, though lacking modern tools, reveals insights into embalming practices and cultural beliefs. De Blasio’s interest in craniology leads to the exploration of cranial deformations, considering as cultural factors. By connecting anthropology with psychology, he questions the cognitive effects of cranial deformations and even associates certain traits with skull morphology. This interplay showcases his ability to merge natural and cultural sciences, offering unique perspectives on human development and cultural practices.